Non-toxic CuInS2 quantum dot sensitized solar cell with functionalized thermoplast polyurethane gel electrolytes - Prakash R.; Das S.; Maiti P. (My University, 2025)
Functionalization of multi-walled carbon nanotubes (CNTs) was carried out through ultrasonication in acidic medium followed by chemical attachment of thermoplastic polyurethane and subsequent chain extension using butane-diol to obtain CNT-tagged polyurethane (PU-CNT). PU-CNT was functionalized by using propane sultone as a sulfonating agent to attach the pendent sulfonate moiety on urethane linkage. The functionalization of CNTs, tagging of CNTs with polymer chain, chain extension and subsequent functionalization of polymer have been confirmed though through spectroscopic techniques such as NMR, FTIR, UV–vis, and Raman spectroscopy. Thermal stability and the nature of interaction is explored through thermal measurements to understand the effect of CNT functionalization. Electrical conduction has been improved by the chemical attachment of CNTs with polymer (1.61 × 10−6 S/cm) which further increases through functionalization (1.37 × 10−4 S/cm) and thereby make them suitable for gel electrolyte. Quantum dot of CuInS2 has been synthesized using DDT as capping agent and its characteristic properties and the dimension are worked out for their suitability as active materials in solar cell. Optical band gap of quantum dots and HOMO/LUMO band structure of functionalized polyurethanes have been measured through UV–vis and cyclic voltametry, and thereby, draw the overall energy diagrams of possible combination of materials. Solar cell devices have been fabricated using the appropriate materials and found improved power conversion efficiency of 0.81% with Au (gold) as counter electrode. The reason behind the better efficiency is understood from the lesser energy gap between HOMO energy level of prepared gel electrolyte (SPU-CNT) and Au (gold) counter electrode, better conductivity and higher rate of hole transportation, to reduce the electron-hole pair recombination. © 2023 Elsevier Ltd